ANALISIS PENERAPAN NILAI DEMOKRASI DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS X IPS SMA NEGERI 1 KERINCI - Febridianti, Annisa; Anderson, Irzal; Kuswanto, Kuswanto (Academy of Education Journal, 2023)
This study aims to describe the application of democratic values ​​in learning Pancasila and citizenship education (PPKn) in class X IPS SMA Negeri 1 Kerinci. This research is focused on the application of democratic values ​​through learning Pancasila and Citizenship Education in class X IPS SMA Negeri 1 Kerinci. Democratic values ​​in learning include the value of cooperation between students, self-confidence, freedom of opinion, mutual respect and respect for differences of opinion. This research was conducted at SMA Negeri 1 Kerinci in March 2023 to completion. This study uses a qualitative method with a descriptive research type. The sampling technique that researchers used in this study was the snowball sampling technique. Data reduction, data presentation and drawing conclusions are data analysis techniques that researchers use in this study. The results of this study are that SMA Negeri 1 Kerinci in class X IPS 1 and 2 the application of democratic values ​​in Civics learning is not fully good enough, this can be seen from the many student behaviors that do not reflect democratic attitudes. The behavior of students in learning activities in class X IPS at SMA Negeri 1 Kerinci is not fully in accordance with the indicators from Zamoni, there are several indicators according to Zamoni which students have not been able to apply in the learning process such as cooperation between students which is still in a poor category, then also attitudes respecting opinions between individuals who are still classified as not good enough, from this, class X IPS has not fully implemented democratic values. So that during the learning process it can be seen that the democratic values ​​highlighted by students are not fully good. On the other hand, the method used by the teacher is the same method every time so it is possible for students to become bored and boring